'A mobile phone is like a friendship. It depends from person to person how it is used': mobile phone relationships among low-income women in urban Bangladesh. Issue 3 (3rd July 2021) - Sibona, Hannah
ABSTRACT: This article presents ethnographic accounts of the mobile phone mediated experiences of connection and intimacy among young low-income women in Dhaka, Bangladesh. It argues that mobile phones are a 'pathway to empowerment' insofar as the ever-evolving social practices of 'wrong-number friendships', long-distance courtship, and the management and manipulation of new contacts on mobile phones broaden the range of social interactions, enable expressions of aspirational mobility, and contribute to the evolution of a sense of self. It also explores how the affective power of mobile phone communication in intimate relationships alters perceptions of distance and creates forms of 'immobile mobility'. Thus, this article builds on research that argues that the material affordances of a mobile phone challenge social and cultural gender norms and power dynamics. Moreover, by drawing out how mobility, gender and class intersect with the social and emotional experiences of low-income women in Bangladesh, it goes beyond existing literature and offers a more nuanced perspective on the notion that access to technology among marginalised and disempowered groups leads to poverty alleviation and greater equality.